2006
DOI: 10.1124/jpet.106.106526
|View full text |Cite
|
Sign up to set email alerts
|

α2C-Adrenergic Receptors Exhibit Enhanced Surface Expression and Signaling upon Association with β2-Adrenergic Receptors

Abstract: The ␣ 2C -adrenergic receptor (␣ 2C AR) is known to be poorly trafficked to the cell surface when expressed in a variety of cell types. We tested the hypothesis that the surface expression and signaling of ␣ 2C AR might be enhanced by heterodimerization with other G protein-coupled receptors (GPCRs). Cotransfection of ␣ 2C AR with more than 25 related GPCRs revealed that only coexpression with the ␤ 2 -adrenergic receptor (␤ 2 AR) increased the surface localization of ␣ 2C AR in human embryonic kidney-293 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Heterodimer pairs studied in such systems include the ANG II AT 1 receptor with bradykinin B 2 receptor (106), AT 2 with B 2 receptor (1), thromboxane ␣-and ␤-receptor (120), dopamine D 1 and D 2 receptors (27), ␣ 2C -and ␤ 2 -adrenergic receptors (92), ␣ 1B -and ␣ 1D -adrenergic receptors (40), and vasopressin V 1a and V 2 receptors (111). This list is far from complete.…”
Section: Et a /Et B Receptor Heterodimerizationmentioning
confidence: 99%
“…Heterodimer pairs studied in such systems include the ANG II AT 1 receptor with bradykinin B 2 receptor (106), AT 2 with B 2 receptor (1), thromboxane ␣-and ␤-receptor (120), dopamine D 1 and D 2 receptors (27), ␣ 2C -and ␤ 2 -adrenergic receptors (92), ␣ 1B -and ␣ 1D -adrenergic receptors (40), and vasopressin V 1a and V 2 receptors (111). This list is far from complete.…”
Section: Et a /Et B Receptor Heterodimerizationmentioning
confidence: 99%
“…For example, the delivery of two subtypes of α-adrenoceptors to the plasma membrane is facilitated by the coexpressed β 2 -adrenoceptor [57,58]; a mutant rhodopsin lacking the targeting sequence is transported to the outer segment only with wild-type rhodopsin [59]. Dimerization could underlie phosphorylation of two coexpressed GPCR subtypes when only one is activated [60,61].…”
Section: Do Gpcr Dimers Have Special Functions?mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that this unique signaling pathway is the result of heterodimerization of the D1 and D2 receptors (Lee et al, 2004). Heterodimerization of ␣ 2C -AR and ␤ 2 -AR has been reported recently in human embryonic kidney 293 cells (Prinster et al, 2006). However, the relevance of this observation to the present study may be limited due to the significant differences in signaling/trafficking between the ␣ 2C -AR and the ␣ 2A -and ␣ 2B -AR present in our neuronal cells.…”
Section: Regulation Of Grk3 Expression 55mentioning
confidence: 99%